THE IMPACT OF THE INFORMATION SOCIETY ON HUMAN RELATIONS - Shakarov Bobur Husniddinovich (Web of Journals Publishing, 2024)
Modern information technology relies on the development of computers and communication tools. Today, the information component is more common in people's daily activities than other components. Therefore, the word "information" has acquired a magical meaning. This term entered the culture of world languages with dozens of forms, combinations and expressions.